COMPARISON OF THE REQUIREMENTS OF WORLD PHARMACOPOEIAS FOR THE QUALITY OF PATCHES - РОЇК, О. М.; БАБЕНКО, Н. О. (Technologies and Engineering, 2023)
The purpose. To conduct a comparative analysis of the requirements of the leading pharmacopoeias for the definition, characteristics, quality indicators and standards, methods and techniques that determine the quality of medical patches as a dosage form. Methodology. The quality indicators of soft preparations for cutaneous use (plasters) are given in the State Pharmacopoeia of Ukraine (SPU) and in foreign pharmacopoeias. The methods of literature analysis, information search, comparison and generalisation were used in the study. Results. A comparison and analysis of pharmacopoeias of the leading countries of the world and the State Fiscal Service of Ukraine regarding the characteristics, classification and quality indicators of patches, depending on their method of application, was carried out. As a result of the scientific analysis, it was found that the requirements for groups of soft dosage forms, which include patches, do not differ in European countries. However, the pharmacopoeias of Japan and the United States provide a detailed discussion of excipients that provide mechanical and technological properties (adhesives and film-forming agents), as well as their description, functional mechanism, chemical properties and general section. The issues of development and standardisation of new modern medicinal products in the form of liquid patches and the need to establish quality indicators for liquid patches are considered. Scientific novelty. Certain discrepancies in the data of world pharmacopoeias regarding the quality control of plasters were established. This is evidence of the need to harmonize the requirements of pharmacopoeias for the unification of techniques and methods of patch analysis, which have found wide application in medicine and pharmacy. Practical significance. The results of the analysis indicate that it is advisable to harmonise pharmacopoeial requirements in order to unify approaches to confirming their quality. However, there is a need for detailed study, standardisation and implementation of new drugs, in particular in the form of liquid patches, which have a number of advantages over other drugs in the treatment of wounds.